Fabrication and Characterization of Graphene Heterostructures with Nitride Semiconductors for High Frequency Vertical Transistors. Issue 10 (13th November 2017) - Giannazzo, Filippo; Fisichella, Gabriele; Greco, Giuseppe; Schilirò, Emanuela; Deretzis, Ioannis; Lo Nigro, Raffaella; La Magna, Antonino; Roccaforte, Fabrizio; Iucolano, Ferdinando; Lo Verso, Stella; Ravesi, Sebastiano; Prystawko, Pawel; et al.
Abstract : The hot electron transistor (HET) is an unipolar majority carrier vertical device with great potential for high frequency (THz) applications. Recently, graphene (Gr) heterostructures with Nitrides have been considered as a promising material system to implement this device concept, with GaN/AlGaN (or GaN/AlN) working as emitter/emitter‐base barrier and Gr as the ultrathin base enabling ballistic transit of hot electrons. In this work, the main issues related to the fabrication of Gr/Nitrides heterojunctions are discussed. An optimized transfer procedure of large‐area Gr membranes onto AlGaN/GaN grown on Si(111) is illustrated. In particular, a soft O2 plasma pretreatment of the AlGaN surface is found to greatly improve the Gr adhesion, resulting in a reduced cracks density. A nanoscale electrical characterization of the obtained Gr/AlGaN/GaN heterostructures was carried out by conductive atomic force microscopy, to evaluate the effect of typical nanometric corrugations (wrinkles) of the Gr membrane on the current transport. These morphological features introduce resistive contributions both to the lateral current transport in the Gr membrane and to the vertical current injection across the heterojunction. The impact of these results on the relevant electrical parameters (i.e., the base resistance and the emitter‐base injection efficiency) of a HET based on this heterostructure is also discussed. Abstract : High resolution structural, morphological and electrical characterization of a graphene junction with an AlGaN/GaN heterostructure . An optimized graphene transfer procedure results in a uniform graphene coverage of the AlGaN surface. The impact of graphene wrinkles on the electrical properties of the heterojunction is investigated by conductive AFM.